Magnitude and determinants of intimate partner violence against women in Somalia: evidence from the SDHS survey 2020 dataset - Abdirizak Hassan Abokor; Omer Adam Farih; Mustafe Abdillahi Ali; Christophe Chesneau; Abdisalam Hassan Muse (BMC Women's Health)
Abstract Background Intimate partner violence (IPV) is a pervasive issue across Sub-Saharan Africa and other developing countries, including Somalia. Understanding the prevalence and drivers of IPV against women is crucial for effective prevention and intervention efforts. However, limited research has focused on identifying these determinants specifically in the Somali context. Purpose This study aims to identify the prevalence and key determinants of IPV in Somalia, including age groups, administrative regions, place of residence, educational level, household size, husband/partner’s education and work, respondent’s work, and total children ever born. Methods Data from the Somali Demographic and Health Survey (SDHS) 2020 were analyzed. Univariate analysis, bivariate analysis and multivariable logistic regression models were used to assess the associations between the identified determinants and IPV. Results The study found significant associations between several factors and IPV. Age, region of residence, type of residence, educational level, husband/partner’s education and work, respondent’s work, and total children ever born were identified as significant determinants of IPV in Somalia. Younger age groups, rural residence, lower educational attainment, unemployment of the husband/partner and respondent, and larger household size were associated with an increased risk of IPV. Conclusion and recommendations The findings highlight the importance of addressing socio-demographic factors to effectively combat IPV in Somalia. Based on the results, recommendations include implementing comprehensive educational programs promoting gender equality and challenging traditional norms, enhancing economic opportunities for women and men, tailoring interventions to address regional disparities, strengthening the legal framework, and improving support services for IPV survivors. Future research should focus on longitudinal studies, qualitative research, intervention evaluation, multi-sectoral collaboration, and the impact of IPV on children. By addressing these recommendations and conducting further research, stakeholders can work towards preventing and reducing IPV in Somalia and other similar contexts.